2018
DOI: 10.18551/erudio.5-1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Baroque Music Exposure on Students During Writing a Narrative Text

Abstract: This research aims to uncover the effects of Baroque music exposure on students during a narrative writing, and is motivated through the popular beliefs of Mozart effect which can enhance human's intelligence and performance in cognitive tasks. This research is conducted from January 18 until February 15, 2018. This research is presented by using qualitative design and method to describe and analyse the result of the interview. The population in this research is the eleventh grader students of Math and Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…Students’ reflections on their music skills development are consistent with research findings showing the positive effects of exposure to baroque music [ 92 , 93 ] and baroque music practice [ 94 ]. Continued and repeated practice is also associated with anatomical changes: neuroimaging findings have shown differences in cellists’ brains when playing contemporary and Baroque styles, suggesting that these various music styles may tap into different cognitive functions [ 108 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Students’ reflections on their music skills development are consistent with research findings showing the positive effects of exposure to baroque music [ 92 , 93 ] and baroque music practice [ 94 ]. Continued and repeated practice is also associated with anatomical changes: neuroimaging findings have shown differences in cellists’ brains when playing contemporary and Baroque styles, suggesting that these various music styles may tap into different cognitive functions [ 108 ].…”
Section: Discussionsupporting
confidence: 83%
“…Whilst the literature extensively covers musical technical skills [ 92 – 94 ] and various types of music ensembles, such as young adult ensembles (e.g., [ 12 ]), research specifically targeting classical music ensembles and their influence on adolescent’s life skills remains scarce. Furthermore, the predominant focus of documented music ensemble experiences revolves around school-based programs [ 33 , 35 ], typically involving children who are already acquainted and share similar social backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Keberadan musik barok ada pada periode antara Renaisans dan Era klasik (Resmana & Anggraeni, 2018). Pada awal abad ke 18 istilah Barok muncul dalam sebuah buku karangan Denis Diderot yang berjudul Encyclopédie.…”
Section: Pendahuluanunclassified
“…Musical intelligence and linguistic intelligence are two key types of intelligence in this theory. Musical intelligence denotes the ability of creativity to facilitate thinking (Ritter & Ferguson, 2017), while writing is one of the creative representations of linguistic intelligence (Al-pop music, instrumental music, and no music, to help with writing processes, while the findings are mixed (Aryanto, 2016;Ransdell & Gilroy, 2001;Resmana & Anggraeni, 2018). These researchers all found that the effect of music type on writing performance is influenced by several factors, such as learners' language proficiency and music preferences.…”
Section: Introductionmentioning
confidence: 99%